Spatial transcriptomics defines injury specific microenvironments and cellular interactions in kidney regeneration and disease - Polonsky, Michal; Gerhardt, Louisa M. S.; Yun, Jina; Koppitch, Kari; Colón, Katsuya Lex; Amrhein, Henry; Wold, Barbara; Zheng, Shiwei; Yuan, Guo-Cheng; Thomson, Matt; Cai, Long; McMahon, Andrew P. (Nature Communications, 2024)
Kidney injury disrupts the intricate renal architecture and triggers limited regeneration, together with injury-invoked inflammation and fibrosis. Deciphering the molecular pathways and cellular interactions driving these processes is challenging due to the complex tissue structure. Here, we apply single cell spatial transcriptomics to examine ischemia-reperfusion injury in the mouse kidney. Spatial transcriptomics reveals injury-specific and spatially-dependent gene expression patterns in distinct cellular microenvironments within the kidney and predicts Clcf1-Crfl1 in a molecular interplay between persistently injured proximal tubule cells and their neighboring fibroblasts. Immune cell types play a critical role in organ repair. Spatial analysis identifies cellular microenvironments resembling early tertiary lymphoid structures and associated molecular pathways. Collectively, this study supports a focus on molecular interactions in cellular microenvironments to enhance understanding of injury, repair and disease.